Friendship and self-harm: a retrospective qualitative study of young adults' experiences of supporting a friend who self-harmed during adolescence - Bilello, Delfina; Townsend, Ellen; Broome, Matthew R.; Burnett Heyes, Stephanie (Frontiers in Psychology, 2024)
Self-harm among young people is becoming increasingly prevalent. Understanding, responding and supporting young people who self-harm is vital. Friends are typically the first and sometimes only source of support sought by adolescents who self-harm. Despite their important role as confidants, friends’ perspectives and experiences remain poorly understood. We conducted retrospective qualitative semi-structured interviews, prompted by an adapted version of the Card-Sort Task for Self-Harm (CaTS-FF), about the experiences of nine female young adults (18-20 years old) who supported a friend who self-harmed during adolescence. Data were analysed using thematic analysis. Four themes were developed: 1) “I did not realise my friend was on the road to self-harm”: Friends’ reactions to self-harm; 2) “That’s what friends do”: The role of friends; 3) The impact of supporting a friend who self-harms; and 4) “They were quite formative years”: Reflecting on growth through the experience. The present findings highlight the complex experiences of young people supporting a friend who self-harms. Despite being willing to take on the role of a supporter, participants experienced a range of difficult emotions and consequences. The temporal transition running through the four themes reflects the evolving nature of participants’ attitudes, knowledge and friendships. Overall, results highlight the unmet needs of adolescents supporting young people who self-harm, as well as identifying potential pathways to ‘support the supporters’ towards resilience.